Analisis Faktor-Faktor Yang Mempengaruhi Terhadap Kepuasan Dan Kinerja Karyawan Di PT Indomarco Prismatama (Indomaret) Batam - Vanness Chuang; Mauli Siagian; Wasiman Wasiman (Prosiding, 2023)
In this era of globalization, competition in the business world is getting tighter, so companies must have the ability to maintain the life and performance of the company. The purpose of this study is to examine the influence of leadership style, compensation, and organizational culture on job satisfaction to improve employee performance. This research was conducted at PT Indomarco Prismatama (indomaret) Batam, the respondents used as many as 146 employees, using Structural Equation Modeling (SEM). The results showed that leadership style, compensation, and organizational culture have a positive and significant influence on job satisfaction in improving employee performance. The influence of the leadership style on job satisfaction is positive and significant, the effect of compensation on job satisfaction is positive and significant, the influence of organizational culture on job satisfaction is positive and significant; and the effect of job satisfaction on employee performance is positive and significant.